The Impact of Multimorbidity Burden, Frailty Risk Scoring, and 3-Directional Morphological Indices vs. Testing for CSF Responsiveness in Normal Pressure Hydrocephalus - Soon, Shereen X. Y.; Kumar, A. Aravin; Tan, Audrey J. L.; Lo, Yu Tung; Lock, Christine; Kumar, Sumeet; Kwok, Janell; Keong, Nicole C. (Frontiers in Neuroscience, 2021)
OBJECTIVE.Multimorbidity burden across disease cohorts and variations in clinico-radiographic presentations within normal pressure hydrocephalus(NPH) confound its diagnosis, and the assessment of its amenability to interventions. We hypothesized that novel imaging techniques such as 3-directional linear morphological indices could help in distinguishing between hydrocephalus vs. non-hydrocephalus and correlate with responsiveness to external lumbar drainage(CSF responsiveness) within NPH subtypes.METHODOLOGY.21 participants with NPH were recruited and age-matched to 21 patients with Alzheimer’s Disease(AD) and 21 healthy controls (HC) selected from the Alzheimer’s Disease Neuroimaging Initiative(ADNI) database. Patients with NPH underwent testing via the NPH programme with external lumbar drainage(ELD); pre- and post-ELD MRI scans were obtained. The modified Frailty Index (mFI-11) was used to stratify the NPH cohort, including Classic and Complex subtypes, by their comorbidity and frailty risks. The quantitative imaging network tool 3DSlicer was used to derive traditional 2-dimensional(2d) linear measures; Evans Index(EI), Bicaudate Index(BCI) and Callosal Angle(CA), along with novel 3-directional(3d) linear measures; z-Evans Index and Brain per Ventricle Ratio(BVR). 3-Dimensional(3D) ventricular volumetry was performed as an independent correlate of ventriculomegaly to CSF responsiveness.RESULTS.Mean age for study participants was 71.14±6.3 years (18, 85.7% males). The majority (15/21, 71.4%) of participants with NPH comprised the Complex subtype (overlay from vascular risk burden and AD); 12/21(57.1%) were Non-Responders to ELD. Frailty alone was insufficient in distinguishing between NPH subtypes. By contrast, 3d linear measures distinguished NPH from both AD and HC cohorts, but also correlated to CSF responsiveness. The z-Evans Index was the most sensitive volumetric measure of CSF responsiveness (p=0.012). Changes in 3d morphological indices across timepoints distinguished between Responders vs. Non-Responders to lumbar testing. There was a significant reduction of indices, only in Non-Responders and across multiple measures (z-Evans Index; p=0.001, BVR at PC; p=0.024). This was due to a significant decrease in ventricular measurement (p=0.005) that correlated to independent 3D volumetry (p=0.008).CONCLUSION.In the context of multimorbidity burden, frailty risks and overlay from neurodegenerative disease, 3d morphological indices demonstrated utility in distinguishing hydrocephalus vs. non-hydrocephalus and degree of CSF responsiveness. Further work may support the characterization of patients with Complex NPH who would best benefit from the risks of interventions.